IMPROVING SUPPLY CHAIN MANAGEMENT SYSTEMS THROUGH THE EFFECTIVE IMPLEMENTATION OF RFID TECHNOLOGY - Vikash; Singh, Dhirendra (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Here, we explore the key elements of RFID technology within a comprehensive supply chain strategy that directly enhances the effectiveness and efficiency of supply chain management. We look at the business processes influenced by RFID, the planning and evaluation necessary for successful implementation, and the potential impacts on supply chain performance. The focus is on the business value and strategic benefits of RFID, as well as the challenges and recommendations for adopting the technology, especially when a company extends its supply chain to upstream suppliers and downstream customers, where external integration is crucial for improving capacity planning and efficiency. By examining four major supply chain processes, we highlight the economic opportunities and challenges associated with integrating RFID into an existing supply chain framework. Our focus is on RFID’s ability to ensure security, privacy, and integrity in supply chain operations while supporting information sharing with suppliers and customers, fostering alliances, forming strategic partnerships, and securing competitive advantages.